2021
DOI: 10.1007/s11033-021-06712-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of chicken cecal microbial diversity and taxonomic composition in response to dietary variation using 16S rRNA amplicon sequencing

Abstract: Antibiotic resistance poses a serious threat to human and animal health. As a consequence, their use in conventional poultry feed may be replaced by non-antibiotic additives (alternatives to antibiotics, ATAs). Phytogenic feed additives and organic acids have been gaining considerable attention that could abate the proliferation of pathogenic bacteria and strengthen gut function in broiler chickens. The aim of this study was to evaluate the effects of phytogenic feed additives and organic acids on cecal microb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 73 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…It is possible that the low protective effectiveness of the KS1 sample is due to the content of potential pathogens of chickens in it, representatives of the Saccharimonadia class (0.01% of the microbiome) or the genus Staphylococcus (0.16% of the microbiome); both of these groups were completely absent in the KS2 sample. There is evidence in the literature about the possibility of the presence of representatives of these groups in the human intestine and the association of their increased proportion in the microbiome with an unfavorable prognosis for diseases [44,45]. The TS2 sample exhibiting a high protective activity, along with the KS1 sample, contained few representatives of Bacilli sensu lato (0.3%, as shown by metagenomic analysis).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is possible that the low protective effectiveness of the KS1 sample is due to the content of potential pathogens of chickens in it, representatives of the Saccharimonadia class (0.01% of the microbiome) or the genus Staphylococcus (0.16% of the microbiome); both of these groups were completely absent in the KS2 sample. There is evidence in the literature about the possibility of the presence of representatives of these groups in the human intestine and the association of their increased proportion in the microbiome with an unfavorable prognosis for diseases [44,45]. The TS2 sample exhibiting a high protective activity, along with the KS1 sample, contained few representatives of Bacilli sensu lato (0.3%, as shown by metagenomic analysis).…”
Section: Discussionmentioning
confidence: 98%
“…The effects of antibiotics and probiotics on the GIT microbiota in chickens were extensively studied by using metagenome sequencing (amplified libraries of 16S rDNA gene fragments were sequenced on the Illumina platform) [29,45]. It has been indicated that in the caeca of broilers, Clostridia are the predominant organisms [30], while the genus Lactobacillus is dominant in the ileum [46].…”
Section: Discussionmentioning
confidence: 99%
“…FSBM affected the intestinal flora, which was associated with intestinal health [48]. Healthy and economically efficient broilers can be produced by regulating the cecal microflora through diet [49][50][51]. Incorporating organic acids into feed had been shown to enhance broiler growth performance, while their synergistic combination with dietary fiber can further augment the humoral immune response [52].…”
Section: Effect Of Fermented Soybean Meal On the Cecal Microbiota Of ...mentioning
confidence: 99%
“…Staphylococcus, Escherichia and Bacillus spp. are associated with the severe food poisoning and foodborne diseases due to the production of toxins produced by some bacteria e.g., B. cereus(Bhattacharyya and Das, 2022) Rashid et al (2021). confirmed microbial load variety on raw chicken meat including pathogens such as E. faecalis, Bordetella spp., Salmonella spp., E. aerogenes, S. aureus, K. pneumoniae, Micrococcus spp., Citrobacter spp., E. coli, S. epidermidis, Proteus spp., K. oxytoca, Providencia spp.…”
mentioning
confidence: 99%